The Early-Roman Period (30 BCE-117 CE) - Hacham, Noah (Walter De Gruyter GmbH, 2022)
Intro -- Acknowledgement -- Table of contents -- List of abbreviations -- Explanatory Note -- Papyri of the Early-Roman Period: Introduction -- Locations where Jews are documented -- Documentary Papyri -- Literary Papyri -- Appendix 1: An additional Jewish papyrus -- Appendix 2: Early-Roman inscriptions -- Appendix 3: Documents not considered Jewish and not included in CPJV -- Indices.